MENGEMBANGKAN METODOLOGI PENEMUAN HUKUM ISLAM âSYARIâAH CUM REALITYâ (Studi Perspektif Historis dan Metodologis) - Ikhsanudin, M. (Al-Mawarid Jurnal Hukum Islam, 2012)
This article discuss on the urgent of developing Islamic law method with syariah cum reality method. This article based on history analysis, through the history of first Islamic law development or the development of Islamic law in Indonesia, and the diversification of Islamic law discover methodology from the ancient schools and contemporary Islamic law scholar. The core of all discuss, itâs needs seriously effort to formulate the Islamic law paradigm, the Islamic law approach, the Methodology of Islamic law discovery and the application of the method on new case of social problem. The expectation of this studies, the transformative, humanize and practice Islamic Law. Not, the dogmatic and formality fiqh. Keywords: Fiqh, Metode Penemuan Hukum, Sejarah Hukum Islam